Kaizen Culture and PM Leadership: Mediating Roles of Morality and Spirituality on Horenso Performance in Indonesian Garment Industry - Galuh Kuswara; Suryana; Syamsul Hadi Senen; Tjutju Yuniarsih (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
A Kaizen work culture that emphasizes continuous improvement and performance-oriented leadership is considered capable of creating a productive, collaborative, and highly moral work environment. This study aims to analyze the influence of a Kaizen work culture and performance-maintenance leadership on Horenso performance, with morality and spirituality as mediating variables in the garment manufacturing industry at a specific company. This research approach used a quantitative method by distributing questionnaires to 75 employees in the warehousing department. Data analysis was performed using structural equation modeling with partial least squares to test the direct and indirect relationships between variables. The results indicate that a Kaizen work culture has a positive and significant effect on Horenso performance, both directly and through morality and spirituality as mediating variables. Similarly, performance-maintenance leadership was shown to have a significant influence on improving Horenso performance by strengthening moral and spiritual values within the workplace. The model explained 68.8 percent of variance in morality and spirituality and 84.2 percent in Horenso performance, with partial mediation effects. Findings indicate moral-spiritual values strengthen Kaizen and performance-maintenance leadership effectiveness in enhancing communication, coordination, collaboration in garment manufacturing.